2020
DOI: 10.1101/2020.06.17.157214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social media reveals consistently disproportionate tourism pressure on a threatened marine vertebrate

Abstract: Establishing how wildlife viewing pressure is distributed across individual animals within a population can inform the management of this activity, and ensure targeted individuals or groups are sufficiently protected. Here, we used social media data to quantify whether tourism pressure varies in a loggerhead sea turtle (Caretta caretta) population and elucidate potential implications. Laganas Bay (Zakynthos, Greece) supports both breeding (migratory, and hence transient) and foraging (resident) turtles, with t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…Creel et al, 2005; Heithaus et al, 2012), turtles must make trade‐offs between accessing optimal resources and evading humans, supporting the risk allocation hypothesis (Lima & Bednekoff, 1999). This finding reinforces the importance of obtaining an evidence base of animal behaviour when human activities are absent, to identify such trade‐offs and quantify potential costs incurred (Papafitsoros et al, 2020; Rutz et al, 2020).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Creel et al, 2005; Heithaus et al, 2012), turtles must make trade‐offs between accessing optimal resources and evading humans, supporting the risk allocation hypothesis (Lima & Bednekoff, 1999). This finding reinforces the importance of obtaining an evidence base of animal behaviour when human activities are absent, to identify such trade‐offs and quantify potential costs incurred (Papafitsoros et al, 2020; Rutz et al, 2020).…”
Section: Discussionsupporting
confidence: 58%
“…Thus, a refuge zone would only be partially effective across any given season (i.e. when conditions coincide with preferred turtle use); yet, it might also form an effective public awareness/education tool with associated economic benefits (Gregr et al, 2020; Papafitsoros et al, 2020; Togridou et al, 2006b). Studies using animal‐borne cameras have also demonstrated that sea turtles scope out potential nesting habitat during the daytime (Fuller et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations